2015
DOI: 10.1007/s13412-015-0238-8
|View full text |Cite
|
Sign up to set email alerts
|

Integrating geoscience into undergraduate education about environment, society, and sustainability using place-based learning: three examples

Abstract: "Integrating geoscience into undergraduate education about environment, society, and sustainability using place-based learning: Three examples" (2015). Papers in the Earth and Atmospheric Sciences. 441. http://digitalcommons.unl.edu/geosciencefacpub/441 Abstract From water to energy, and from climate change to natural hazards, the geosciences (marine, Earth, and atmospheric science) have an important role to play in addressing a wide range of societal issues, with particular relevance to how humans can live su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Furthermore, instructors can incorporate additional data into each module (e.g., from the National Snow and Ice Database), providing opportunities for place‐based learning (Gosselin et al. ), particularly valuable if course or institution resources are limited or field trips are infeasible.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, instructors can incorporate additional data into each module (e.g., from the National Snow and Ice Database), providing opportunities for place‐based learning (Gosselin et al. ), particularly valuable if course or institution resources are limited or field trips are infeasible.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that indigenous students tend to approach scientific questions through observations and reflections based on casual questions (Beck et al, 1996;Cajete, 2000). Semken (2005) (Gosselin et al, 2016). Each example used a different approach to present ES concepts relating to the particular challenge to the local area.…”
Section: )mentioning
confidence: 99%
“…All examples supported that place-based learning helped students apply classroom knowledge to their lives. Gosselin (2016) and his colleagues concluded that place-based settings are extremely useful at building problem-solving skills when ES is taught under other contexts such as economy, society, community and policies, since it facilitates critical thinking, questioning, reflections and knowledge and skills acquisition.…”
Section: )mentioning
confidence: 99%
“…The language training gives them some confidence to read and engage with locals and native speakers (Allen 2010, Kinginger 2011. The concept of high-impact place-based learning, putting concepts in a specific geo-physical space (Gosselin et al 2016), is central to this objective. For Sustainable China, the syllabus for the prerequisite course includes authors the students will meet in China and case studies of the places they will visit.…”
Section: Preparingmentioning
confidence: 99%